Case Report: Wound Closure Acceleration in a Patient With Toxic Epidermal Necrolysis Using a Lyophilised Amniotic Membrane - Lipový, Bretislav; Hladík, Martin; Štourač, Petr; Forostyak, Serhiy (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Toxic epidermal necrolysis (TEN) is a rare life-threatening disease that mainly affects the skin and mucous membranes, resulting from a toxic delayed-type hypersensitivity (DTH) reaction (type IV reaction) to the presence of foreign antigens such as drugs. The clinical symptoms are caused by pathophysiological processes leading to massive apoptosis of keratinocytes in the dermo-epidermal junction. This results in the formation of a bulla and subsequent separation of the entire epidermis with the exposure of the dermis. The current approach in the local therapy of TEN prefers the use of biological dressings, which helps provide several critical requirements for defect healing; in particular, it helps in the acceleration of the spontaneous wound closure (re-epithelialization) of the skin defect and the reduction of the risk of development of various complications and infections, such as the risk of pathological scar maturation. This paper is a case report of the use of a lyophilized amniotic membrane (AM) for accelerating wound healing in a patient with TEN. Case Presentation: We report a case of an 8-year-old girl transferred to our center with a histologically confirmed diagnosis of TEN. Despite the application of immunosuppressive therapy consisting of corticosteroids and intravenous immunoglobulins, we have observed disease progression and exfoliation of up to 60% of the total body surface area (TBSA). In the facial area, which is cosmetically privileged, we decided to use the lyophilized amniotic membrane (Amnioderm®) to cover up approximately 2% of the TBSA. Within 2 days after the application, we observed accelerated reepithelialisation, with rapid wound closure. We have not observed any side effects nor infections during the subsequent phases of wound healing. Skin defects in non-facial areas of the body were treated with synthetic dressings. When compared to the areas covered with the lyophilized AM, the healing process was prolonged. Conclusions: To our knowledge, this is the first case study using a lyophilized amniotic membrane in the treatment of a patient with TEN. The AM application in the cosmetically-privileged area (face), proved to be very efficient in the treatment of TEN patients. The use of this allogeneic material demonstrated excellent biocompatibility and caused a unique acceleration of epithelialization and wound healing, yielding also excellent long-term results. The current study opens broad possibilities for clinical application of the used material, the improvement of current therapy of patients with TEN and better outcomes and recovery of patients.